Fundamentals of Clinical Data Science - Kubben, Pieter; Dumontier, Michel; Dekker, Andre; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This open access book comprehensively covers the fundamentals of clinical data science, focusing on data collection, modelling and clinical applications. Topics covered in the first section on data collection include: data sources, data at scale (big data), data stewardship (FAIR data) and related privacy concerns. Aspects of predictive modelling using techniques such as classification, regression or clustering, and prediction model validation will be covered in the second section. The third section covers aspects of (mobile) clinical decision support systems, operational excellence and value-based healthcare. Fundamentals of Clinical Data Science is an essential resource for healthcare professionals and IT consultants intending to develop and refine their skills in personalized medicine, using solutions based on large datasets from electronic health records or telemonitoring programmes. The book$1 (Bs promise is (3z(Bno math, no code(3y(Band will explain the topics in a style that is optimized for a healthcare audience.s
Data sources -- Data at scale -- Standards in healthcare data -- Using FAIR data / data stewardship -- Privacy / deidentification -- Preparing your data -- Creating a predictive model -- Diving deeper into models -- Validation and Evaluation of reported models -- Clinical decision support systems -- Mobile app development -- Operational excellence -- Value Based Healthcare (Regulatory concerns).
Keywords: Medical informatics; Bioinformatics; Health Informatics; Computational and Systems Biology